2016
DOI: 10.3390/polym8050179
|View full text |Cite
|
Sign up to set email alerts
|

Poly(Acrylic acid)–Based Hybrid Inorganic–Organic Electrolytes Membrane for Electrical Double Layer Capacitors Application

Abstract: Nanocomposite polymer electrolyte membranes (NCPEMs) based on poly(acrylic acid)(PAA) and titania (TiO 2 ) are prepared by a solution casting technique. The ionic conductivity of NCPEMs increases with the weight ratio of TiO 2 .The highest ionic conductivity of (8.36˘0.01)ˆ10´4 S¨cm´1 is obtained with addition of 6 wt % of TiO 2 at ambient temperature. The complexation between PAA, LiTFSI and TiO 2 is discussed in Attenuated total reflectance-Fourier Transform Infrared (ATR-FTIR) studies. Electrical double lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 53 publications
4
20
0
Order By: Relevance
“…Substantial differences were seen on the lignin/caprolactone biodegradable film surface and it was found that the LL‐37 peptide was placed successfully on the biodegradable film surface. Similar SEM micrographs have been reported in the literature 33 …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Substantial differences were seen on the lignin/caprolactone biodegradable film surface and it was found that the LL‐37 peptide was placed successfully on the biodegradable film surface. Similar SEM micrographs have been reported in the literature 33 …”
Section: Resultssupporting
confidence: 89%
“…The sp 3 C‐H stretching mode of PAA and PCL shows two broad band regions at 2855 and 2945 cm −1 . These peaks in the spectrum are consistent with the literature 25,33 . In the spectrum of lignin/caprolactone biodegradable film after LL‐37 peptide immobilization (Figure 3B) show new absorption bands at 1640 (amide I) and 1555 cm −1 (amide II).…”
Section: Resultssupporting
confidence: 89%
“…For the LCST hydrogels, as shown in Figure S4a, Supporting Information, higher intensity peak at 1565 cm −1 was observed, demonstrating the higher content of COO − . Indeed, LCST hydrogel was formed with the addition of larger amount of Na 2 CO 3 , leading to more COO − and thereby a large content of hydrogen bonds between water and CO in COO − groups . When the temperature was increased, the tremendous water/CO hydrogen bonds were destroyed that can be confirmed by the larger decrease in the IR intensity of the COO − peak (Figure S4a, Supporting Information) .…”
mentioning
confidence: 86%
“…However, the major risks of liquid electrolytes include low cyclic retention due to the highly corrosive nature of electrolytes and their leakage; this deteriorates the device stability, reliability, and safety . On the other hand, solid polymer electrolytes (SPEs) provide the advantages of compactness and reliability without the leakage of liquid components, but their low ionic conductivity hinders the performance of their devices . In addition to this, usage of nondegradable polymer electrolytes in large amount is hazardous to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, two types of fillers, copper(II) oxide (CuO) and yttrium(III) oxide (Y 2 O 3 ) nanoparticles, were used in this study. CuO, which is a d‐block element with the electronic configuration [Ar]3d4s, was chosen because of its low toxicity, large abundance, low cost, antimicrobial activity, and desirable optical, electrical, and electrochemical properties. Its merits have been proven through its applications in gas sensors, electrode materials for supercapacitors, solar cells, catalysts for electrochemical activities, and lithium batteries .…”
Section: Introductionmentioning
confidence: 99%